2017
DOI: 10.1128/jvi.02100-16
|View full text |Cite
|
Sign up to set email alerts
|

Virion Structure of Black Queen Cell Virus, a Common Honeybee Pathogen

Abstract: Viral diseases are a major threat to honeybee (Apis mellifera) populations worldwide and therefore an important factor in reliable crop pollination and food security. Black queen cell virus (BQCV) is the etiological agent of a fatal disease of honeybee queen larvae and pupae. The virus belongs to the genus Triatovirus from the family Dicistroviridae, which is part of the order Picornavirales. Here we present a crystal structure of BQCV determined to a resolution of 3.4 Å. The virion is formed by 60 copies of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 78 publications
4
54
0
Order By: Relevance
“…Virus-receptor binding and genome release can be prevented when inhibitors bind to this pocket (33,34). Considering the lack of the hydrophobic pocket in VP1, similar to other reported dicistroviruses (7,8,11,12), MCDV shall have different receptor binding sites. A previous report has revealed that the finger-like protuberance of TrV plays roles in virus-host interactions (8), whereas the C terminus of MCDV VP3 occupies the location of finger-like protuberance.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Virus-receptor binding and genome release can be prevented when inhibitors bind to this pocket (33,34). Considering the lack of the hydrophobic pocket in VP1, similar to other reported dicistroviruses (7,8,11,12), MCDV shall have different receptor binding sites. A previous report has revealed that the finger-like protuberance of TrV plays roles in virus-host interactions (8), whereas the C terminus of MCDV VP3 occupies the location of finger-like protuberance.…”
Section: Resultssupporting
confidence: 51%
“…Besides MCDV, structures of four other viruses from the family Dicistroviridae have been determined to date ( Fig. 3): Israeli acute bee paralysis virus (IAPV) (11), triatoma virus (TrV) (8), black queen cell virus (BQCV) (12), and cricket paralysis virus (CrPV) (7). Among these, a stable VP4 disk-like structure was seen only in IAPV and CrPV, while atomic models could not be built for TrV and BQCV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicochemical properties of both f. Iflaviridae and f. Dicistroviridae have not been fully established . However, phylogenetic analyses based on the virion structure comparing honeybee iflaviruses and dicistroviruses to picornaviruses showed that DWV and BQCV are structurally related to vertebrate picornaviruses (f. Picornaviridae ) . In general, picornaviruses are considered to be relatively resistant to chemical germicides, mainly as a consequence of the absence of the lipid envelope of virions .…”
Section: Introductionmentioning
confidence: 99%